2000
DOI: 10.1164/ajrccm.161.5.9904119
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hypoventilation and Ventilation-Perfusion Redistribution in Oxygen-induced Hypercapnia during Acute Exacerbations of Chronic Obstructive Pulmonary Disease

Abstract: The detailed mechanisms of oxygen-induced hypercapnia were examined in 22 patients during an acute exacerbation of chronic obstructive pulmonary disease. Ventilation, cardiac output, and the distribution of ventilation-perfusion (V A/Q ) ratios were measured using the multiple inert gas elimination technique breathing air and then 100% oxygen through a nose mask. Twelve patients were classified as retainers (R) when Pa(CO(2)) rose by more than 3 mm Hg (8.3 +/- 5.6; mean +/- SD) after breathing 100% oxygen for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
102
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(104 citation statements)
references
References 14 publications
1
102
0
1
Order By: Relevance
“…This is only a significant risk when the inspired oxygen concentration exceeds y30% (30 kPa). The mechanism underlying this process has been hotly debated since the 1960s [27], with evidence supporting ventilation/perfusion mismatching in very severe cases [28], whereas CO 2 retention in less severe episodes involves an element of hypoventilation secondary to a reduction in hypoxic drive to breathing [29]. Controlled oxygen can be safely administered via a Venturi-based face mask or through nasal prongs.…”
Section: Maintaining Gas Exchangementioning
confidence: 99%
“…This is only a significant risk when the inspired oxygen concentration exceeds y30% (30 kPa). The mechanism underlying this process has been hotly debated since the 1960s [27], with evidence supporting ventilation/perfusion mismatching in very severe cases [28], whereas CO 2 retention in less severe episodes involves an element of hypoventilation secondary to a reduction in hypoxic drive to breathing [29]. Controlled oxygen can be safely administered via a Venturi-based face mask or through nasal prongs.…”
Section: Maintaining Gas Exchangementioning
confidence: 99%
“…This leads to a subsequent increase in functional dead space. This hypothesis was supported in a later study by Robinson et al 7 Others found that hyperoxia also lessens the hyperventilation that follows acute hypercapnia in subjects with COPD. 8 Still others found the increase in P aCO 2 from hyperoxia to be a function of both increased functional dead space and decreased ventilatory response to hypercapnia.…”
mentioning
confidence: 64%
“…9 Additionally, patients with COPD are not a homogenous group; it seems that there are subjects who retain (ie, become hypercapnic when hyperoxemic) and those who do not. 7 We know that subjects who are more hypoxemic and hypercapnic on room air experience greater degrees of hypercapnia with hyperoxia. 10 In this issue of RESPIRATORY CARE, we add a new study to the existing disarray.…”
mentioning
confidence: 99%
“…Robinson et al 26 used the multiple inert gas elimination technique to measure ventilation, cardiac output, and the distribution of ventilation-perfusion ratio in patients with a COPD exacerbation. They found that in patients in whom P aCO 2 rises in response to 100% oxygen, ventilation decreases and alveolar dead space increases.…”
Section: Discussionmentioning
confidence: 99%